1996
DOI: 10.3905/jfi.1996.408184
|View full text |Cite
|
Sign up to set email alerts
|

Cointegration, Common Factors, and the Term Structure of Yen Offshore Interest Rates

Abstract: Critical values are for the 1% significance level. These values are obtained fiom Zhang [1993] and can be computed as cx2 (2m2) where c = 0.85 -0.58/(2m2) as described in Joharxen [1988]. The sample period is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In their empirical analyses, they found that there are three principal factors in the yield curve: the level, the steepness and the curvature. Bühler and Zimmermann [4], and Hiraki, Shiraishi and Takezawa [5] also indicated similar conclusions. Other than these, there have been plenty of studies applying PCA to interest rates.…”
Section: Introductionsupporting
confidence: 66%
“…In their empirical analyses, they found that there are three principal factors in the yield curve: the level, the steepness and the curvature. Bühler and Zimmermann [4], and Hiraki, Shiraishi and Takezawa [5] also indicated similar conclusions. Other than these, there have been plenty of studies applying PCA to interest rates.…”
Section: Introductionsupporting
confidence: 66%
“…Previous work has found that the yield curve is well-summarized by three factors that respectively shift its level, its slope and its curvature (see e.g. Litterman and Scheinkman (1988), Singleton (1994) and Hiraki, Shiraishi and Takezawa(1996)). We also assume a three-factor model of the Japanese yield curve.…”
Section: Reduced Form Vector Auto-regressionmentioning
confidence: 99%
“…Third, the study will provide an insight into the long-term equilibrium relationship between different maturity classes of Thai and US government bonds. Historically, studies investigating long-term equilibrium relationships have been restricted to securities of developed countries (Hiraki et al, 1996).…”
Section: Introductionmentioning
confidence: 99%